Geotechnics of organic soils and peat - Huat, B.B.K.; Prasad, A.; Asadi, A.; Kazemian, Sina (2014)
Peat and organic soils commonly occur as extremely soft, wet, unconsolidated surficial deposits that are an integral part of wetland systems. These types of soils can give rise to geotechnical problems in the area of sampling, settlement, stability, in situ testing, stabilisation and construction. There is therefore a tendency to either avoid building on these soils, or, when this is not possible, to simply remove or replace soils, which in some instances can lead to possibly uneconomical design and construction alternatives. However, in many countries of the world, these soils cover a substantial land area and pressure on land use is resulting in ever more frequent utilisation of such marginal grounds. For the successful design, construction and performance of structures on such marginal soils, it is crucial to predict geotechnical behaviour in terms of settlement, shear strength and stability, with respect to time. This means expanding our knowledge base and calls for a reliable characterisation of their geotechnical properties and mechanical behaviour and subsequently, the devising of suitable design parameters and construction techniques for dealing with these materials. A sound scientific understanding of the nature and functions of peat and organic soils is critical to their correct and safe use, and this book contributes by offering students, researchers, engineers and academics involved with these types of soils a comprehensive overview. This book will be useful not only to those in the field of geotechnical engineering, but also to soil scientists and agriculturalists, who are involved in the development of peatlands.